Rekonstruksi Pemikiran dan Posisi Sufi-Antisufi Ibn TaymÄ«yah - Zamzami, Mukhammad (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2017)
This article reanalyzes Ibn Taym?yah?s position and his thought in Sufism and anti-Sufism. The article is also expected to find the precise typology to describe the qualification of Ibn Taym?yah?s Sufism other than the Sunn? and Falsaf? typologies. As a formalist and literalist thinker, Ibn Taym?yah has been famously known as an anti-Sufi Muslim scholar. There have been a number of modern Salafis who refute any relationship of Ibn Taym?yah and Sufism. Ibn Taym?yah has criticized such philosophical doctrines of Sufism as wa?dat al-wuj?d, ?ul?l, and itti??d, which are considered to have deviated from the foundations of Islam. Along with his criticism, Ibn Taym?yah offers solution by recovering the earliest and authentic traditions of Sufism when it is viewed as to have obscured the authenticity of knowledge based on the al-Qur??n and Sunnah. The product of his Sufism can be, therefore, categorized in Salafi-Sufism typology in addition to other such pIbn Taym?yahopular typologies as Sunn? and Falsaf?. The pattern of the Ta?awwuf Salaf??which is deemed as being appropriate to describe the existence of Ibn Taym?yah?s Sufism?does not, basically, accept takwil upon the religious texts. The aim of his Sufism is to strengthen one?s faith and help him/her to purify their soul and morality